Intransitive Permutation Groups with Bounded Movement Having Maximum Degree - Razzagh, Behnam (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
Let G be a permutation group on a set with no fixed points in and let m be a positive integer. If for each subset of the size is bounded, for , we define the movement of g as the max over all subsets of . In this paper we classified all of permutation groups on set of size 3m + 1 with 2 orbits such that has movement m . 2000 AMS classification subjects: 20B25